PENERAPAN PENDEKATAN SAINTIFIK PADA MATA PELAJARAN SENI BUDAYA DI SD NEGERI 2 SEGALAMIDER BANDAR LAMPUNG - Yohana Ria Ismono; Susi Wedhaningsih; Amelia Hani Saputri (STKIP Subang, 2026)
The purpose of this study was to describe the steps of implementing the scientific approach in Arts and Culture learning at SD Negeri 2 Segalamider Bandar Lampung based. This research employed a descriptive qualitative method. Data were collected through observation, with data presented through interviews, and documentation. The data obtained from of the teacher and 21 fourth-grade students at SD Negeri 2 Segalamider Bandar Lampung. Data analysis techniques included data collection, data reduction, conclusion drawing, and verification. The results indicated that the teacher had implemented the five steps of the scientific approach (5M) in the maximum category. These steps included: the observing stage through video screenings and material presentations; the questioning stage by providing stimulus questions based on the surrounding environment; the experimenting stage through student worksheets (LKPD) on classifying two-dimensional art principles; the associating stage through advanced assignments for deeper understanding; and the communicating stage through presentations of batik mask creations documented in video format. Overall, the implementation of the scientific approach at SD Negeri 2 Segalamider has proceeded systematically in accordance with lesson planning, despite the school being in a curriculum transition period.